A Study of the Causal role of the Soul in the Process of Perception, From Mulla Sadra’s Standpoint - Reza Ghasemian (حکمت اسرا, 2014)
In contrast to his predecessors, who considered a passive role for the perceptive power, Mulla Sadra moved towards considering a causal role for it. From his perspective, the soul is like an inventor while having sensual and fantastic perceptions, which makes perceptive figures in the domain of the soul. The prerequisite for Mulla Sadra’s assertion is for knowledge to be taken out of the essential realm and to be transformed into an existential issue, because making a cause upon an effect is particular to existence. Still, believing in the causality of the soul regarding the forms that it does not possess, would lead to problems, such as the violation of the principle “The Giver of something must possess it”, which aresolvable by drawing upon the issue of non-material being.